ANALISIS SPASIAL PERUBAHAN TUTUPAN LAHAN PASCA KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN MUARO JAMBI - Maruddani, Rizki Feroza; Somantri, Lili; Panjaitan, Frandica (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Changes in land use and cover play an important role in sustainable natural resource management. Muaro Jambi Regency, which is rich in biodiversity, has ecosystem services for residents in the area, especially plantations which are one of the leading commodities. Forests as the largest land cover in Muaro Jambi Regency have experienced quite rapid changes, especially after forest and land fires occur almost every year. Real-time monitoring and assessment on a spatio-temporal basis is important to determine changes in land cover. This research examines changes in land cover in Sarolangun Regency from Landsat-8 time series images from 2018 to 2023. Land cover is classified into 6 classes using the supervised classification method. The data findings show that forests have experienced a significant decline, while settlements have experienced a very substantial increase. Comprehensive research regarding the vulnerability of periodic land cover changes at local and regional levels must be carried out to maintain sustainable environmental ecosystems.